Longitudinal stream synoptic monitoring tracks chemicals along watershed continuums: a typology of trends - Kaushal, Sujay S.; Maas, Carly M.; Mayer, Paul M.; Newcomer-Johnson, Tammy A.; Grant, Stanley B.; Rippy, Megan A.; Shatkay, Ruth R.; Leathers, Jonathan; Gold, Arthur J.; Smith, Cassandra; McMullen, Evan C.; Haq, Shahan; et al. (Frontiers in Environmental Science, 2023)
There are challenges in monitoring and managing water quality due to spatial and temporal heterogeneity in contaminant sources, transport, and transformations. We demonstrate the importance of longitudinal stream synoptic (LSS) monitoring, which tracks combinations of water quality parameters along flowpaths across space and time. Specifically, we analyze stream synoptic patterns of chemical mixtures of carbon, nutrients, greenhouse gasses, salts, and metals concentrations along 10 longitudinal flowpaths draining 1,765 km2 of the Chesapeake Bay region. These 10 longitudinal stream flowpaths are drained by watersheds experiencing either urban degradation, forest and wetland conservation, or stream and floodplain restoration. Along the 10 longitudinal stream flowpaths, we monitored over 300 total sampling sites along a combined stream length of 337 km. Synoptic monitoring along longitudinal flowpaths revealed: (1) increasing, decreasing, stepwise, piecewise, or no trends and transitions in water quality with increasing distance downstream, which provide insights into water quality processes along flowpaths; (2) longitudinal trends in chemical concentrations along flowpaths can be quantified and compared using simple linear and nonlinear mathematical relationships with distance downstream and land use/land cover attributes, (3) attenuation and transformation of chemical cocktails along flowpaths depend on: spatial scales, pollution sources, and transitions in land use and management, hydrology, and restoration. We compared our LSS patterns with others from the global literature to synthesize a typology of longitudinal water quality trends and transitions in streams and rivers based on hydrological, biological, and geochemical processes. Applications of LSS monitoring along flowpaths from our results and the literature reveal: (1) longitudinal sources of nonpoint and point pollution along streams and rivers, (2) if pollution sources spread further downstream to sensitive receiving waters such as drinking water supplies and coastal zones, and (3) if transitions in land use, conservation, management, or restoration can attenuate downstream transport of pollution sources. Our typology of longitudinal water quality responses along flowpaths combines many observations across suites of chemicals that can follow predictable patterns in the context of watershed characteristics and provides a foundation for future studies, evaluating management and restoration efforts, and comparing responses to nonpoint and point source pollution across watersheds and regions.